Turbot TNF-α gene: molecular characterization and biological activity of the recombinant protein [Poster] - Ordás, M. Camino; Costa, M. M.; Dios, S.; Roca, F. J.; López-Castejón, G.; Mulero, Victoriano; Meseguer, José; Figueras Huerta, Antonio; Novoa, Beatriz (2006)
Poster.-- 10th Congress of the International Society of Developmental and Comparative lmmunology, July 1‐6, 2006, Charleston, South Carolina, USA No